2011
DOI: 10.21161/mjm.24110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate and culture conditions on the production of amylase and pullulanase by thermophilic Clostridium thermosulforegenes SVM17 in solid state fermentation

Abstract: The endo acting enzyme with dual specificity towards -1,4-and -1,6-glycosidic linkages are named as amylopullulanase. The production of extracellular thermostable amylopullulanase by Clostridium thermosulfurogenes SVM17 was investigated in solid state fermentation (SSF). Coarse type wheat bran was found to be the best substrate among ten easily available complex organic substrates evaluated. The production of enzyme reached a peak in 72 h. A high level of enzyme was produced in wheat bran moistened with PYE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The best substrate for xylanase production was wheat bran due to its nutritional content and large surface area [ 29 ], where wheat bran contained xylan and protein, which were served as carbon and nitrogen sources for microorganisms, respectively [ 30 ]. α-Amylase was also exhibited the maximum production by Clostridium thermosulforegenes using wheat bran [ 31 ]. Wheat bran characterized by its better air circulation, loose particle binding and efficient penetration by mycelia and cheaper, therefore it showed a better prospect economically in fermentation processes [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The best substrate for xylanase production was wheat bran due to its nutritional content and large surface area [ 29 ], where wheat bran contained xylan and protein, which were served as carbon and nitrogen sources for microorganisms, respectively [ 30 ]. α-Amylase was also exhibited the maximum production by Clostridium thermosulforegenes using wheat bran [ 31 ]. Wheat bran characterized by its better air circulation, loose particle binding and efficient penetration by mycelia and cheaper, therefore it showed a better prospect economically in fermentation processes [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the maximum saccharification content of total soluble carbohydrates (140 mg/g solid) and reducing sugars (55 mg/g solid) was observed at 70 and 80% moisture, respectively (Figure 3 b). Other results showed that the yield of α-amylase and amylopullulanase by Clostridium thermosulfurogenes increased with an increase in solid to moistening agent ratio from 1:0.5 to 1:2.5 (30 to 75%) with a maximum at 1:2.25 (73%) [ 31 ]. Optimum xylanase production from Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Different agricultural residues were used as substrates and among those substrates, wheat bran showed the maximum synthesis of α-amylase by using Bacillus megatherium in SSF. Clostridium thermosulforegenes provided the highest synthesis of α-amylase by utilizing wheat bran (Mrudula et al, 2011). Due to the loose binding of wheat bran particles, air can easily circulate among them.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SSF has fewer chances of contamination because most contaminants cannot survive in the absence of low water activity. After process optimization in SSF, bacterial species such as Bacillus licheniformis ( Khalaf and Aldeen., 2013 ) and Clostridium thermosulforegenes ( Mrudula et al, 2011 ) produced pullulanase effectively. The feasibility of using SSF to produce the enzyme on a large scale, however, was not investigated ( Akassou and Groleau, 2019 ).…”
Section: Approaches Used To Increase Pullulanase Yieldmentioning
confidence: 99%